KEBEBASAN EKSPRESI KEAGAMAAN DI JOGJA CITY OF TOLERANCE (STUDI KASUS TOLERANSI DAN INTOLERANSI DI BALIK PLANK “TERIMA KOST PUTRA MUSLIM/PUTRI MUSLIMAH”) - Muryana Muryana (UIN Sunan Kalijaga Yogyakarta, 2017)
Jogja City of Tolerance proceed approximately twelve years. But, discriminate based on religion still happen. On the one side it was human rights, but in the other side it taked another human rights. In the case of some boarding houses sometimes the owner put sentence such as “kost putri muslimah” in front of the homestay to informate someone who will rent. It can be assumtion that different religion couldn’t be the tenant for this boarding houses. Whereas city of tolerance could be assumed that the member of city had multiculturalism perspective. Parekh affirmed that significant aspect of multikulturalism was politic of recognition. Accordingly, this paper will answer two question: firstly, why sentence such as “kost putri muslimah” put in some boarding houses; secondly, how tolerance means in this context. The answer explanation of two questions above was got from interview and photo documentation of boarding houses in Sleman and Kota Yogyakarta. It analyzed using Parekh’s theory, politic of recognition in multiculturalism. Based on the research, result was got that the owner of boarding houses have several reasons put the sentence. Firstly, they had trauma with different etnicity. So, sensitivity of religion was used to safe. Secondly, they lived together with the tenant and they had education vision to the them. Therefore, tolerance has its context. The recognition to the other depends on their interest as the owner to keep their environtment. In this context human rights relates to other human rights in togetherness. Human right could do in general.